Enhancing Writing Skills through Cultural Integration: Exploring the Impact of Culturally-Responsive Writing Instruction in Diverse EFL Classrooms - Sutrisno, Djoko; Abbas, Azwar; Nafi Annury, Muhammad (Global Synthesis in Education Journal, 2024)
In an increasingly multicultural and interconnected world, the integration of culturally-responsive teaching methods into English as a Foreign Language (EFL) instruction has emerged as a vital pedagogical approach. This study examines the impact of culturally-responsive writing instruction on the development of EFL learners' writing skills, comparing it with traditional writing instruction. The objective is to explore how integrating cultural elements into writing pedagogy enhances linguistic competencies, fosters engagement, and promotes inclusivity in diverse classrooms. A mixed-methods research design was employed, combining a quantitative pre-test and post-test experimental approach with qualitative interviews and focus group discussions. The quantitative phase of the study involved assessing writing performance in two groups: one experimental group that received culturally-responsive instruction and one control group that followed traditional teaching methods. Writing samples were evaluated using standardized rubrics to measure key competencies such as content, organization, grammar, and critical thinking. The qualitative phase gathered insights into students' perceptions, motivation, and engagement through thematic analysis of interviews and focus group discussions. The results demonstrated significant improvements in the experimental group's writing performance, with notable gains in grammar (+40.9%), critical thinking (+41.7%), and vocabulary (+35.3%). Students reported higher engagement, confidence, and personal connection to writing tasks. Teachers observed improved participation and deeper critical analysis in student writing. However, challenges such as balancing curriculum demands and limited institutional support were highlighted. Overall, the findings underscore the transformative potential of culturally-responsive instruction in improving writing outcomes, fostering cultural appreciation, and creating inclusive learning environments. This study contributes to the growing body of evidence advocating for educational equity and culturally-responsive practices in EFL classrooms.